2022
DOI: 10.3389/fvets.2022.920755
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in wing geometry among Tabanus rubidus (Diptera: Tabanidae) populations in Thailand

Abstract: Tabanus rubidus (Wiedemann, 1821) (Diptera: Tabanidae) is a hematophagous insect of veterinary and medical importance and is the predominant Tabanus spp. in Thailand. It is a potential mechanical vector of Trypanosoma evansi, which causes surra in domestic and wild animals. Wing geometric morphometrics is widely used as morphological markers for species identification and to assess the insect population structure. Herein, we investigated the intraspecific variation in wing geometry among T. rubidus populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Hence, we do not suggest using the wing size to distinguish these flies if the sex of the flies is unknown. In fact, it has also been shown that the wing size is unsuitable for the differentiation of insect species because it is frequently influenced by environmental factors ( Jirakanjanakit et al, 2007 ; Morales Vargas et al, 2010 ; Baleba et al, 2019 ; Phanitchat et al, 2019 ; Chaiphongpachara et al, 2022b ; Chaiphongpachara et al, 2022c ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we do not suggest using the wing size to distinguish these flies if the sex of the flies is unknown. In fact, it has also been shown that the wing size is unsuitable for the differentiation of insect species because it is frequently influenced by environmental factors ( Jirakanjanakit et al, 2007 ; Morales Vargas et al, 2010 ; Baleba et al, 2019 ; Phanitchat et al, 2019 ; Chaiphongpachara et al, 2022b ; Chaiphongpachara et al, 2022c ).…”
Section: Discussionmentioning
confidence: 99%
“…It is a quantitative method for measuring the size and shape variation through landmark-, semilandmark-, and outline-based analyses ( Dujardin 2008 ; Dujardin et al, 2014 ; Dujardin and Dujardin, 2019 ). The GM method can be used to identify species and evaluate differences within species (intraspecific variation) and between sexes (sexual dimorphism) in several insects of medical and veterinary importance ( Ruangsittichai et al, 2011 ; Lorenz et al, 2012 ; Sontigun et al, 2017 ; De Souza et al, 2020 ; Oliveira-Christe et al, 2020 ; Simões et al, 2020 ; Changbunjong et al, 2021 ; Martinet et al, 2021 ; Chaiphongpachara et al, 2022a ; Chaiphongpachara et al 2022b ; Chaiphongpachara et al 2022c ; Laojun et al, 2023 ). The efficiency of GM for species identification has been demonstrated in stomoxyine flies ( Stomoxys spp.)…”
Section: Introductionmentioning
confidence: 99%
“…To test the validity of global size for accurate species identification, we used a maximum likelihood approach based validated reclassification approach ( 59 ). The allometric effect (the effect of size on shape variation) was performed by linear regression of the first (shape derived) discriminant factor on the CS, and then estimated by the determination coefficient r 2 ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…WGM is largely developed in several vectors families like as Culicidae [see review of Lorentz et al ( 29 )] to explore intraspecific variations among mosquito populations or to research interspecific variation, to study in sexual dimorphism, plasticity and deviation, to detection of parasites and to characterize laboratory strain. This technique was used to study the intra specific variations in Glossinidae ( 30 ), Muscidae ( 31 ), Psychodiae ( 28 , 32 , 33 ), Reduviidae ( 34 ) and Tabanidae ( 35 , 36 ) and to show inter specific variations in Muscidae ( 37 ). The landmark-based WGM analysis of Culicoides wings has proven to be a valuable tool for interspecific discrimination ( 38–42 ), C. circumscriptus intersexes specimens ( 43 ), sexual dimorphism ( 44 ) and geographic variations ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this method include: low cost, high precision ( Dujardin, 2008 ). In the past decade, the application of this technique has expanded to horse flies from various regions, highlighting differences between species that are sometimes indistinguishable by morphological characteristics and barcoding alone ( Torres & Miranda-Esquivel, 2016 ; Changbunjong et al, 2021 ; Chaiphongpachara et al, 2022 ; Mullens et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%